2020
DOI: 10.34119/bjhrv3n4-014
|View full text |Cite
|
Sign up to set email alerts
|

Coinfecção HIV-Sífilis nos pacientes acompanhados em um serviço de atenção especializado de João Pessoa-PB

Abstract: Objective: To describe the sociodemographic and clinical profile of patients with HIV-Syphilis co-infection followed up at a Reference Service in the city of João Pessoa-PB between April 2017 and April 2018.Method: The study was cross-sectional, observational, retrospective and descriptive, with the collection of information from medical records, using an authoritative and standardized form. The study population consisted of patients diagnosed with HIV between April 2017 and April 2018.Results: The diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
0
1
Order By: Relevance
“…HIV and syphilis co-infection was mainly prevalent in men, with a mean age of 36.9 years, single, and homosexual or bisexual; these results corroborated several studies 5,8 . The mean age of women with co-infection was lower (31.3 years) than men, possibly due to HIV diagnosis during pregnancy.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…HIV and syphilis co-infection was mainly prevalent in men, with a mean age of 36.9 years, single, and homosexual or bisexual; these results corroborated several studies 5,8 . The mean age of women with co-infection was lower (31.3 years) than men, possibly due to HIV diagnosis during pregnancy.…”
Section: Resultssupporting
confidence: 88%
“…Studies observed that HIV increases five times the risk of reinfection by syphilis 24 , while individuals with a history of syphilis have a 3.5-fold higher risk of reinfection 25 . The present study showed that 39.1% of the individuals had a recurrence of syphilis, a percentage higher than in other studies 8 .…”
Section: Resultscontrasting
confidence: 71%